Two NIU undergraduates learned the Malay Language at UMP - UMP, PNC
Two undergraduates from Northern Illinois University (NIU) in the US - Matthew Ropp, 21, and Derek Koegel, 22, were so proud to be able to speak better Malay after undergoing a six-week Malay Language programme for international students (BMfIS) that focused on authentic communication.